2008
DOI: 10.1007/s10482-008-9282-7
|View full text |Cite
|
Sign up to set email alerts
|

Four novel Candida species in the Candida albicans/Lodderomyces elongisporus clade isolated from the gut of flower beetles

Abstract: Flower-visiting beetles belonging to three species of Cetoniidae were collected on three mountains near Beijing, China, and yeasts were isolated from the gut of the insects collected. Based on the 26S rDNA D1/D2 domain and internal transcribed spacer (ITS) region sequence analysis and phenotypic characterization, four novel anamorphic yeast species located in the Candida albicans/Lodderomyces elongisporus clade were identified from 18 of the strains isolated. The new species and type strains are designated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The latter three yeast species were isolated from insects collected in Panama and USA (Nguyen et al2007;Suh et al 2008) (Fig 1A). The tree topology is in agreement with topologies obtained previously based on analysis of LSU rDNA (Ji et al 2009) and combined sequences of LSU rDNA and SSU rRNA (Kurtzman & Suzuki 2010). Statistical support for the major branches was, however, low in both studies.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The latter three yeast species were isolated from insects collected in Panama and USA (Nguyen et al2007;Suh et al 2008) (Fig 1A). The tree topology is in agreement with topologies obtained previously based on analysis of LSU rDNA (Ji et al 2009) and combined sequences of LSU rDNA and SSU rRNA (Kurtzman & Suzuki 2010). Statistical support for the major branches was, however, low in both studies.…”
Section: Resultssupporting
confidence: 90%
“…Members of the clade were isolated from various sources, such as marine habitats, food, plants, and soil (Lachance et al 2011;Nitiyon et al 2011;Nakase et al 2009;Limtong et al 2012;Sipicszki 2013), soft drinks (Chang et al 2012), and human and animals (Weems 1991;Wingard 1995;Trofa et al 2008;Cooper 2011;Kim & Sudbery 2011;Lachance et al 2011a). Studies conducted in different geographic regions showed that insects frequently host yeasts belonging to the Lodderomyces clade, including the human pathogens (Nguyen et al 2007;Suh et al 2008;Ji et al 2009, Urbina 2012. The discovery of additional new yeast species in the Lodderomyces clade is important for a better understanding of its taxonomy and the evolution of pathogenecity in yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…In a complementary study, four novel anamorphic yeast species were isolated from the gastrointestinal tracts of flower-visiting beetles in China (17). These novel insect-associated Candida species closely cluster with the human fungal pathogen Candida albicans/Lodderomyces elongisporus clade (17). The emergence of human pathogenic Cryptococcus species from an ancestral lineage of mycoparasitic and insect frass-associated fungi might be similar to these previously illustrated examples in the ascomycetes.…”
Section: Discussionmentioning
confidence: 77%
“…In a complementary study, four novel anamorphic yeast species were isolated from the gastrointestinal tracts of flower-visiting beetles in China (17). These novel insect-associated Candida species closely cluster with the human fungal pathogen Candida albicans/Lodderomyces elongisporus clade (17).…”
Section: Discussionmentioning
confidence: 99%
“…elongisporus, named after Dr Jacomina Lodder, is a yeast first described in 1952 as Saccharomyces elongasporus (van der Walt, 1966). It has been isolated in nature from Californian citrus concentrates and the alimentary tract of flower-visiting beetles and other insects and was first described as a bloodstream isolate in 2008 (Ji et al, 2009;Lockhart et al, 2008;Nguyen et al, 2007). This organism was found after a small percentage of isolates confirmed by Vitek and API 20C (bioMérieux) as Candida parapsilosis gave unexpected CHROMagar results.…”
Section: Discussionmentioning
confidence: 99%